2014
DOI: 10.1002/esp.3576
|View full text |Cite
|
Sign up to set email alerts
|

The impact of beaver dams on the morphology of a river in the eastern United States with implications for river restoration

Abstract: Restoration projects in the United States typically have among the stated goals those of increasing channel stability and sediment storage within the reach. Increased interest in ecologically based restoration techniques has led to the consideration of introducing beavers to degraded channels with the hope that the construction of beaver dams will aggrade the channel. Most research on beaver dam modification to channels has focused on the long‐term effects of beavers on the landscape with data primarily from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Levine and Meyer (2014) reported large sediment losses but the remnants of the dam structure were found to trap sediment, which was rapidly colonised by plants and stabilised. In contrast, other studies have observed rapid loss of pond sediments following dam collapse (Curran and Cannatelli, 2014;Levine and Meyer, 2014). It is likely that, as with the site studied, where closely-spaced, multi-dam complexes exist, these will provide a major buffering effect, reducing the likelihood of dam failure and, in so doing, also reducing the downstream release of sediment from any single dam failure.…”
Section: Total Sediment and Nutrient Storagementioning
confidence: 85%
“…Levine and Meyer (2014) reported large sediment losses but the remnants of the dam structure were found to trap sediment, which was rapidly colonised by plants and stabilised. In contrast, other studies have observed rapid loss of pond sediments following dam collapse (Curran and Cannatelli, 2014;Levine and Meyer, 2014). It is likely that, as with the site studied, where closely-spaced, multi-dam complexes exist, these will provide a major buffering effect, reducing the likelihood of dam failure and, in so doing, also reducing the downstream release of sediment from any single dam failure.…”
Section: Total Sediment and Nutrient Storagementioning
confidence: 85%
“…The effects of beaver dams on in‐channel entrainment thresholds and transport rates are similar to those described for other forms of LW. Beaver dams decrease sediment entrainment and transport within the backwater zone upstream from the dam (Butler and Malanson, ; John and Klein, ; De Visscher et al , ), enhance bed scour where flow plunges over a dam (Pollock et al , ), enhance spatial variation in average bed grain size (Curran and Cannatelli, ), and can create substantial pulses of sediment transport when a dam fails (Butler and Malanson, ; Russell et al , ).…”
Section: Existing Knowledge Of Wood and Sediment Dynamicsmentioning
confidence: 99%
“…Previous research has shown the ability of beaver dams to have a significant impact on each of these areas. As a result, many restoration projects are beginning to use beaver and beaver dam structures as an ecological and cost‐effective approach in restoration and management (Andersen & Shafroth, ; Burchsted et al , ; Curran & Cannatelli, ; DeBano & Heede, ; DeVries et al , ; Pollock et al , ).…”
Section: Discussionmentioning
confidence: 99%